Demethylation of dimethylsulfoniopropionate to 3-S-methylmercaptopropionate by marine sulfate-reducing bacteria. - van der Maarel, M J (1996)
The initial step in the anaerobic degradation of the algal osmolyte dimethylsulfoniopropionate (DMSP) in anoxic marine sediments involves either a cleavage to dimethylsulfide and acrylate or a demethylation to 3-S-methylmercaptopropionate. Thus far, only one anaerobic bacterial strain has been shown to carry out the demethylation, namely, Desulfobacterium sp. strain PM4. The aims of the present work were to study how common this property is among certain groups of anaerobic bacteria and to obtain information on the affinities for DMSP of DMSP-demethylating strains. Screening of several pure cultures of sulfate-reducing and acetogenic bacteria showed that Desulfobacterium vacuolatum DSM 3385 and Desulfobacterium niacini DSM 2059 are also able to demethylate DMSP; a very slow demethylation of DMSP was observed with a salt-tolerant strain of Eubacterium limosum. From a 10(5) dilution of intertidal sediment a new marine DMSP-demethylating sulfate-reducing bacterium (strain WN) was isolated. Strain WN was a short, gram-negative, nonmotile rod that grew on betaine, sarcosine, palmitate, H2 plus CO2, and several alcohols, organic acids, and amino acids. Extracts of betaine-grown cells had hydrogenase, formate dehydrogenase, and CO dehydrogenase activities but no alpha-ketoglutarate oxidoreductase activity, indicating the presence of the acetyl coenzyme A-CO dehydrogenase pathway. Analysis of the 16S rRNA gene sequence of strain WN revealed a close relationship with Desulfobacter hydrogenophilus, Desulfobacter latus, and Desulfobacula toluolica. Strain PM4 was shown to group with Desulfobacterium niacini. The K(m) of strain WN for DMSP, as derived from substrate progress curves in cell suspensions, was approximately 10 microM. A similar value was found for D. niacini PM4.